The Language of the Gukurahundi Genocide in Zimbabwe: 1980-1987. Issue 2 (3rd April 2021) - Sibanda, Brian
Summary: The Gukurahundi genocide in Zimbabwe claimed more than 20 000 lives in the Matebeleland and Midlands provinces of the country at the hands of the state and its militia for political and tribal reasons. This article seeks to demonstrate how language, through hate speech, naming, symbolisation, dehumanisation, and classification, justified and rationalised Gukurahundi. While the linguistic conventions used by state actors before and during Gukurahundi did not cause genocide, it created two social climates, one that legitimised tribal and political hatred, thus eliminating any social sanctions preventing genocide and the other that unmasked the state-sponsored genocide clothed as a necessary military exercise against dissidents. This article employs Allport's (1954) Scale of Prejudice and Stanton's (2016) eight stages of genocide as a tool of making sense of the social processes that create society's progression from prejudice and discrimination to genocide; how through language conventions, the unthinkable becomes acceptable through the erosion of moral, social, religious and rational boundaries. Linguistic conventions show how power is enacted through discourse, how language acts prepare and maintain the way for physical and material acts, and how the same language conventions generate permissions for Gukurahundi, the Rwanda genocide and the Holocaust, amongst others. To demonstrate the permissibility conditions for non-linguistic behaviours like Gukurahundi, this article addresses the metaphor of Gukurahundi, the dehumanisation of the victims, political and religious constructions and the re-construction of the 'other'.